The roles of waqf in social development: A conceptual review - Nurul Aien, Abd Aziz; Noraina Mazuin, Sapuan; Puteri Fadzline, Muhamad Tamyez; Nurliana Nasution, ST MKom (GBMR, 2025)
Purpose: The purpose of this study is to explore the role of waqf in fostering social development, particularly in the sectors of education, healthcare, and economic development. It highlights waqf's historical significance and contemporary relevance, illustrating its contributions to human capital development, public health, and sustainable economic growth. Design/methodology/approach: This study employs a conceptual review by synthesizing findings from a wide range of academic literature and historical records to understand the waqf's impact comprehensively. Findings: The study finds that waqf significantly contributes to bridging educational gaps, enhancing healthcare accessibility, and promoting sustainable economic growth. In education, waqf supports infrastructure and financial needs, fostering human capital development. It funds hospitals and health centers, ensuring services for marginalized populations. From the economic aspect, waqf coin poverty alleviation supports micro-entrepreneurs and stabilizes incomes during crises, facilitating equitable wealth distribution and financial inclusion. Research limitations/implications: The study is limited by the availability and scope of existing literature, which may not cover all potential impacts of waqf. The conceptual review relies on secondary data, which can introduce biases and limit the depth of analysis. Furthermore, due to economic, social, and political changes, the historical data may not fully reflect the waqf's current and future potential. Empirical research and primary data collection are needed to validate the findings and precisely quantify Waqf's contributions. Practical implications: The findings underscore the importance of leveraging waqf as a strategic social and economic development tool. Policymakers and practitioners can utilize these insights to enhance the effectiveness of waqf in addressing contemporary socio-economic challenges, ensuring sustainable development and social welfare. Originality/value: This study comprehensively analyzes waqf's role in societal advancement, integrating historical and contemporary perspectives through a conceptual review. It highlights waqf's adaptability and enduring relevance, offering valuable insights into its potential as a transformative instrument for education, healthcare, and economic development in various contexts.